Building Future Innovators: Single Valued Neutrosophic t-Conorm for Evaluating the Role of College English Education in Entrepreneurial Skill Development - Chun Ye (Neutrosophic Sets and Systems)
The growing significance of entrepreneurial education within higher learning institutions necessitates innovative methodologies for assessing its effectiveness—especially when integrated with core subjects such as English education. This paper proposes a Single Valued Neutrosophic (SVN) t-Conorm-based multi-criteria decision-making (MCDM) approach to evaluate how English courses contribute to entrepreneurial skill development. The model accommodates uncertainty, indeterminacy, and vagueness in human judgments, essential when assessing educational outcomes like creativity, communication, and innovation. By incorporating subjective and linguistic input from students and educators, the framework offers a holistic and granular analysis. Two MCDM methods are used in this study such as CRITIC method to compute the criteria weights using the correlation values and the MULTIMOORA method to rank the alternatives using three parts: ratio system, reference point, and full multiplicative form. This proposed approach is validated using an application. This approach helps policymakers and educators enhance pedagogical strategies aligned with innovation and entrepreneurship goals.